PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SMP NEGERI 6 MELIAU - Syaparani, Syaparani (Universitas Tanjungpura, 2019)
AbstractThis research background is based on the fact that education of reading still low and provide direction and efforts which was done by teacher in implementation model cooperative integrated reading and composition of student class VII. Research use deskriptif method, with qualitative research approach and classroom action research design.The research subjects were students in class VII of Meliau Middle School 6 as many as 30 people. Data sources are obtained from students and teachers in the form of observation guidelines, written tests, and documentation.Implementation cooperative integrated reading and composition models successfully improve students' reading comprehension skills. The completeness of the group's average value in the first cycle is 73,4% and cycle second 87,3%, while the individual completeness in the first cycle is 77%, and cycle second 100%. Keywords: Cooperative integrated reading and composition, understanding reading ability